2020
DOI: 10.1101/2020.02.17.951574
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anode surface bioaugmentation enhances deterministic biofilm assembly in microbial fuel cells

Abstract: Microbial fuel cells (MFCs) are devices that can generate energy while aiding biodegradation of waste through the activity of an electroactive mixed biofilm. Metabolic cooperation is considered essential for MFCs’ efficiency, especially during early-anode colonization. Yet, the specific ecological processes that drive the assembly of an optimized anode-attached community remain unknown. Here, we show, using 16S rRNA gene amplicon and shotgun metagenomic sequencing that bioaugmentation of the anode surface with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The similarity between economics and microbial behaviour even goes further, as trading of essential resources between microorganisms can accelerate the total growth of the microbial community (Tasoff et al ., 2015). In an open system, in which immigration of new microorganism can influence microbial assembly and function in the receiving engineered or natural ecosystem (Mei and Liu, 2019; Dottorini et al ., 2021), the complete process is carried out with more accuracy and a higher efficiency by multiple species than on an individual basis, as for example illustrated in anode biofilm assembly in microbial fuel cells (Yanuka‐Golub et al ., 2021).…”
Section: Effective Abilities Of Mixed Microbial Communities For Engin...mentioning
confidence: 99%
“…The similarity between economics and microbial behaviour even goes further, as trading of essential resources between microorganisms can accelerate the total growth of the microbial community (Tasoff et al ., 2015). In an open system, in which immigration of new microorganism can influence microbial assembly and function in the receiving engineered or natural ecosystem (Mei and Liu, 2019; Dottorini et al ., 2021), the complete process is carried out with more accuracy and a higher efficiency by multiple species than on an individual basis, as for example illustrated in anode biofilm assembly in microbial fuel cells (Yanuka‐Golub et al ., 2021).…”
Section: Effective Abilities Of Mixed Microbial Communities For Engin...mentioning
confidence: 99%
“…Phylogenetic analysis of this colony revealed that additional bacterial species were present (Supplementary Figure S3), therefore, we referred to it as a highly enriched electroactive consortium. Then, the colonies were applied on clean anodes by spreading the colony onto the anode surface, and then these anodes were inoculated inside MFCs [30]. Figure 5 compares the lag time and time to reach steady-state current density for all experimental sets conducted in this study.…”
Section: Direct Application Of An Anode Enrichment Consortium Reducesmentioning
confidence: 99%